Answer:
we cant see the qeastion
Step-by-step explanation:
First, you would have to add d to both sides to get rid of it
x+d=ab+c/b
Then you would multiply b by both sides to get rid of the b in the denominator
x+d(b)=ab+c
After that, you would subtract c from both sides
x+d(b)-c=ab
Then you would divide both sides by a
x+d(b)-c=b
------------
a
Write out the equation;
y=a^b
y=(-2)^2
y=(-2)(-2)
y=4
Therefore, the value of a^b is 4
Hope I helped :)
Answer:
3(x/4) - 1/2 (x/10) or you can just do 0.7x but I don't think that counts as an expression, so just put 3(x/4) - 1/2 (x/10).
Step-by-step explanation: